The Phenomenon Of Quite Quitting In The World Of Work: A Sociological Perspective On The Change In The Professional Ethos Of Generation Z - Hastuti, Puji; Wahyuningrat, Wahyuningrat; Setianto, Akbar Yuli (Socious Journal, 2025)
The phenomenon of quiet quitting describes a phenomenon where employees only fulfill tasks according to job descriptions without taking further initiative, as a response to changes in social values and expectations of the workplace. This study explores the phenomenon of quiet quitting in the context of changes in the professional ethos of Generation Z with a sociological approach. The results of the study indicate that quiet quitting is not only related to burnout or exhaustion, but also a reflection of the mismatch between employee expectations and work reality. Generation Z prioritizes work-life balance, mental health, flexibility, and inclusivity, which is in contrast to a work culture that prioritizes excessive hard work. In this context, alienation theory suggests that lack of recognition, control, and meaning in work can trigger quiet quitting behavior. This study proposes that organizations need to adjust their policies and leadership styles to create a work environment that is more supportive of employee well-being and engagement, which in turn will improve performance and loyalty to the company